The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/dbp.0b013e31828c5f88
|View full text |Cite
|
Sign up to set email alerts
|

Spina Bifida Grown Up

Abstract: The majority of people with spina bifida in the United States are now older than 18 years of age. Health care delivery for adults with this condition should include routine surveillance for common conditions such as hypertension, hyperlipidemia and cancer. It should also address spina bifida-related complications such as pressure sores, lymphedema, sexual dysfunction and infertility, and hydrocephalus, as well as chiari-related symptoms such as sleep apnea and urologic and renal functioning. Almost all adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 57 publications
1
29
0
1
Order By: Relevance
“…Recommended medical summary components are medical and surgical history, current care plans, emergency care plans, medications, allergies, vaccines, current providers, cognitive/physical function, and selfmanagement assessment [33]. Condition care plans document the date of diagnosis, severity of condition and/or associated comorbidities, previous pertinent evaluations and interventions, provider (s) managing the condition, and the current management.…”
Section: Medical Summarymentioning
confidence: 99%
“…Recommended medical summary components are medical and surgical history, current care plans, emergency care plans, medications, allergies, vaccines, current providers, cognitive/physical function, and selfmanagement assessment [33]. Condition care plans document the date of diagnosis, severity of condition and/or associated comorbidities, previous pertinent evaluations and interventions, provider (s) managing the condition, and the current management.…”
Section: Medical Summarymentioning
confidence: 99%
“…34,36,37,83,[87][88][89] Outcomes are variable: Children with OTSC having a 50% rate of UDS improvement, SCM improving in 1/3 and complex LMM only 11% improvement. 57,[89][90][91][92] Infants and young children tend to have better UDS improvement than those undergoing surgery later in childhood. 35,56,77,93…”
Section: Urologic Outcomementioning
confidence: 99%
“…Studies on transition to adult care have suggested that successful transitions are associated with adequate pre-transition patient preparation, flexible timing of transition, early introduction to the adult clinic, and invested and coordinated adult providers 3,30 Similarly, school-to-work transitions require professional support, social support, consideration of transportation needs, and assistance coping with medical comorbidities, stigma, learning disabilities and executive dysfunction. 17,18 …”
Section: Discussionmentioning
confidence: 99%